1987
DOI: 10.1177/026921558700100207
|View full text |Cite
|
Sign up to set email alerts
|

Disabled patients in acute hospital wards

Abstract: Seventy-five patients who had a clinically diagnosed disabling disease and who usually had difficulty with one or more activities of selfcare were identified in a 10-month survey of the acute wards of a large teaching hospital. Their dependence on assistance for specific activities at home and in the acute wards was recorded by a research nurse in interviews carried out in the patient's home within two weeks of hospital discharge. The study showed that although most of the disabled patients were able to contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A study in Edinburgh showed that limitations in the provision of facilities on the ward led to increased dependence by the patients on the nurses. 6 The haphazard provision of ward toilet rails has been observed elsewhere.7 A survey of 140 elderly people at home showed 5% using raised toilet seats, a further 8% needing them, 9% using a fixed toilet rail, and a further 11% needing one. 8 One survey found that 33% of people over 75 at home used toilet aids and 43% of women over 85 could not get to the toilet without aids or personal assistance.9 Such people are disadvantaged when admitted to hospitals where…”
Section: Had None Lockingmentioning
confidence: 97%
See 1 more Smart Citation
“…A study in Edinburgh showed that limitations in the provision of facilities on the ward led to increased dependence by the patients on the nurses. 6 The haphazard provision of ward toilet rails has been observed elsewhere.7 A survey of 140 elderly people at home showed 5% using raised toilet seats, a further 8% needing them, 9% using a fixed toilet rail, and a further 11% needing one. 8 One survey found that 33% of people over 75 at home used toilet aids and 43% of women over 85 could not get to the toilet without aids or personal assistance.9 Such people are disadvantaged when admitted to hospitals where…”
Section: Had None Lockingmentioning
confidence: 97%
“…Toilet:bed ratio 1:3 to 1:4 1:26 to 1: [6][7][8] Standard met only on psychogeriatric ward. Worst ratio on 3 geriatric wards Signposting Clear signposting by words and symbols Only 1 toilet signposted Labelling Large clear labelling on door 10 Had small labels; 7…”
mentioning
confidence: 99%
“…In the old and the disabled there is evidence for both deconditioning and increased dependency in hospital (Hoenig and Rubenstein 1991;Creditor 1993). Sklaroff (1987) reports an increased dependency in hospital, compared with home, due to limitations in the provision and use of ward facilities. Sklaroff (1987) reports an increased dependency in hospital, compared with home, due to limitations in the provision and use of ward facilities.…”
Section: Negative Aspects Of Hospital Carementioning
confidence: 99%
“…In acute wards, access to the toilet may be difficult because furniture, equipment and visitors' chairs are stored near access routes. 1 Even in a rehabilitation ward, wheelchair users complained that the lavatories were cramped. 2 Toilets may be cold, stark and ill-equipped.…”
mentioning
confidence: 99%
“…Only one-third of hospital inpatients who normally used a high-seat chair at home were provided with one in hospital. 1 In every other case, nurses had to help the patients in and out of their chairs, thereby diminishing the patients' independence and increasing the nurses' workload.…”
mentioning
confidence: 99%